From mechanics to Digital Materiality: Paradigmatic turns in the design process in architecture (ARQUISUR Revista, 2019)
The adoption and adaptation of digital tools in architecture have configured an intense process of assimilation of their own logic. The digital turn in architecture could be understood as the one that replaces the architecture of industrialization with the architecture of information, but, and, above all, the one that goes from thinking in mechanical terms to doing it in algorithmic and digital terms. The effects of digitization on architecture, as a historical disciplinary process, are characterized in two previous stages, as two turns of the digital in architecture in the process that goes from mechanics to Digital Materiality (M.D.). The present article intends to advance in conceptual precisions from the selection and analysis of texts focused on the understanding and explanation of a complex process whose gestation has been going on for several decades, M.D. as the current stage of assimilation of the digital logics in the processes of architectural ideation.
Keywords: algorithms, architectural project, digital manufacturing, digital variability, parametric design